Study of Spray Fogging Performance Using a Combination of Fogging Machine, Electric Sprayer, and Air Blower - Gatot Pramuhadi; Josua Natanael; Nenda Fuji Putri Daliesta (The University of Lampung, 2025)
This study aims to determine and analyze the parameters of spray fogging performance for the application of pesticide fog. Air blower spraying performance can be increased by regulating the type of fan and type of air blower. Setting the type of fan in air blower is axial fan and centrifugal combined with cone of 4, 6, and 8 holes. The most optimum combination of the test treatment is the combination of axial fan air blower and 4-hole cone. Spray fogging can be increased by adjusting the combination spray angle between fogging machines and air blowers at various observation distances. The combination spray angle setting is angle of 15°, 30°, and 45° and the observation distance of 1 meter to 4 meters. The results of the analysis and determination of spray fogging performance parameters produce an angle of 45° as the most optimum spray angle from the observation distance of 1 meter to 4 meters. This is indicated by the average value of the droplet diameter of 78.74 μm, a 70 droplet/cm2 droplet density, an air flow speed of 1.97 m/s, and the temperature of the flocking of 31.8℃. Keywords: Air blower, Droplets, Fogging, Nozzle, Spray.